Menggunakan Teks sebagai Sarana Adaptasi Sosial - Dessy Wahyuni (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
Communication has been a part of human life. as social beings, people always want to get connected. In other words, communication is fundamental for a person in social life. When communicating, people deliver messages to others. in order for the messages to be delivered, text with which language is the medium is required. Therefore, text has a very important role as a means of social adaptation. In 2013, Agency of Language Development and Fostering launched 2013 curriculum with text-based-learning scheme to bring a new paradigm for education in Indonesia. Textual learning enables children to resolve real-life problems with critical thinking and to engage with social adaptation. in the process of adaptation,individual delivers thoughts, ideas, messages through text with which language is the medium. This study used descriptive method to obtain the description of text use as a means of social adaptation. by examining Indonesia Language Textbook in I, IV, VII, and X grade, it can be concluded that every text has different social function together with different communication purpose among human beings.